Pharmacodynamic monitoring by residual gene expression of the nuclear factor of activated T cell-regulated genes in lung transplant recipients and its correlation with tacrolimus blood levels - Boada-Pérez, Meritxell; Ruiz de Miguel, Victoria; Erro, Marta; Ussetti, Piedad; Aguilar, Myriam; Castejón, Raquel; Rosado, Silvia; Escobar-Fornieles, Roser; Revilla-López, Eva; Bravo, Carlos; Sáez-Giménez, Berta; Zapata-Ortega, Marta; et al. (Frontiers in Immunology, 2024)
Trough blood levels (C0) of tacrolimus are used to adjust drug dosage, but they do not consistently correlate with clinical outcomes. Measurement of residual gene expression of nuclear factor of activated T cell (NFAT)-regulated genes (NFAT-RGE) has been proposed as a pharmacodynamic biomarker to assess the degree of immunosuppression in certain solid organ transplantations, but little is known regarding lung transplant recipients (LTR). Our primary objective is to correlate tacrolimus blood levels with NFAT-RGE. NFAT-RGE and tacrolimus C0 and peak (C1.5) levels were determined in 42 patients at three, six and 12 months post-transplantation. Tacrolimus C0 did not exhibit a correlation with NFAT-RGE, whereas C1.5 did. Besides, over 20% of measurements indicated high levels of immunosuppression based on the below 30% NFAT-RGE threshold observed in many studies. Among those measurements within the therapeutic range, 19% had an NFAT-RGE<30%. Consequently, a subset of patients within the tacrolimus therapeutic range may be more susceptible to infection or cancer, potentially benefiting from NFAT-RGE and tacrolimus peak level monitoring to tailor their dosage. Further quantitative risk assessment studies are needed to elucidate the relationship between NFAT-RGE and the risk of infection, cancer, or rejection.